The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-3180.2011.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an injection system on the effect of activated soil steaming on Brassica juncea and the natural weed seedbank

Abstract: Soil steaming is a promising preventive method for weed control in high-value cash crops, such as vegetables and flowers. A 2-year experiment (2005)(2006) was carried out to test the effect of five different systems of steam injection (surface or deep steam injection bar and three mixed systems at different steam distribution ratios between the surface and the deep bar: 1:2; 1:1 and 2:1) on an artificial infestation of Brassica juncea and on the natural weed seedbank. Treatments were carried out using steam al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Our machine requires less energy and a lower operative time compared with mobile broad-steaming machines (Gay et al 2010b;Peruzzi et al 2011). However, the biological results obtained with our band-steaming machine are not directly comparable with that obtained by Gay et al (2010b) and Peruzzi et al (2012). Gay et al (2010b) used a broad steam machine equipped with hoods combined with sub-surface steam injectors.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our machine requires less energy and a lower operative time compared with mobile broad-steaming machines (Gay et al 2010b;Peruzzi et al 2011). However, the biological results obtained with our band-steaming machine are not directly comparable with that obtained by Gay et al (2010b) and Peruzzi et al (2012). Gay et al (2010b) used a broad steam machine equipped with hoods combined with sub-surface steam injectors.…”
Section: Discussionmentioning
confidence: 87%
“…The actual dose, computed on the full width of the machine was 1886 kg ha -1 . The CaO dose was chosen based on previous experience (Peruzzi et al, 2012) such as that which combined with steam gave the highest soil temperatures and weed control values. Lenzi, Lombardi, and Tesi (2004) indicated that CaO can be used in association with steam without production risks, provided that the application dose not exceeds 4000 kg ha -1 .…”
Section: Machine Set Up For Field Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many techniques have been developed to transfer thermal energy to soil. Generally, they rely on two concepts—the use of solar energy (Horowitz et al , ; Linke, ) and steam (Kolberg & Wiles, ; Melander & Jørgensen, ; Bàrberi et al , ; Peruzzi et al , ). Solar energy and steam reduce weed emergence from the soil seedbank through exposure to moderate temperatures for long periods (44–55°C for up to 6 weeks) and to high temperatures for short periods (90–100°C for just minutes), respectively (Linke, ; Bàrberi et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…For better results, chemical additives with exothermic reactions like potassium hydroxide (KOH) or calcium oxide (CaO) are sometimes used (Barberi et al, 2002;Barberi et al, 2009). For example, the patented bioflash system uses a self-propelled machine to disinfect soil in greenhouses by incorporating steam and additives with a rotary hoe into tilled soil Peruzzi et al, 2011;Peruzzi et al, 2012). Neither in Swiss nor in European organic farming is the outdoor-use of such additives allowed.…”
Section: Introductionmentioning
confidence: 99%